2020
DOI: 10.7759/cureus.6577
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Major Depression with Body Mass Index and Salivary Cortisol

Abstract: Open Access Original Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
3
10
1
Order By: Relevance
“…Tashakori et al, 43 in their study where they examined the relationship between BMI and depression, stated that individuals who were slightly obese (25BMI < 30) experienced moderate depression and individuals who were obese (BMI>30) experienced major depression. [40][41][42][43] This finding obtained in the study is similar to the findings made before the pandemic.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Tashakori et al, 43 in their study where they examined the relationship between BMI and depression, stated that individuals who were slightly obese (25BMI < 30) experienced moderate depression and individuals who were obese (BMI>30) experienced major depression. [40][41][42][43] This finding obtained in the study is similar to the findings made before the pandemic.…”
Section: Discussionsupporting
confidence: 87%
“…30,39 In the study, it was found that students with mild obesity had higher levels of depression. Khan et al 40 stated that there was a positive and statistically significant relationship between BMI and major depression in the study in which they examined the relationship between major depression and BMI. Pahali et al, 41 in their study where they examined the relationship between psychiatric diseases and BMI, stated that the mean score of depression scale was higher than other individuals and that there was a statistically significant relationship between BMI and depression score.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, it should be noted that the presence of abdominal fat-since chronically high levels of cortisol have been associated with depression through abdominal fat presence [11]-is present in the majority of these patients [12], and is linked to a worse prognosis [13]. Specifically, it is the active cortisol in free form which goes through the cellular membrane, the one positively correlated with fat percentage [14], and mainly from the abdominal region due to a higher expression of 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) in this region [15]. Since it is a molecule of a fat-soluble nature, levels of free cortisol (approximately 6%) [16] depend globulin (GBP, globulin binding protein) which mostly carries it [17], as well as and the albumin which carries it by 14% [18].…”
Section: Introductionmentioning
confidence: 99%
“…Taking all the aforementioned into account, the aim of this study was to establish the impact of the administration of EGCG, supplemented with coconut oil in cortisol activity, and its relations with possible improvements in the perception of depression associated with abdominal fat loss. lated with fat percentage [14], and mainly from the abdominal region due to a higher expression of 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) in this region [15]. Since it is a molecule of a fat-soluble nature, levels of free cortisol (approximately 6%) [16] depend globulin (GBP, globulin binding protein) which mostly carries it [17], as well as and the albumin which carries it by 14% [18].…”
Section: Introductionmentioning
confidence: 99%
“…The cortisol level in saliva has become a striking subject in recent years [ 11 ]. The amount of cortisol is higher in saliva as compared to serum, thus, the salivary cortisol level provides a better understanding of related depression [ 12 ]. Cortisol is a glucocorticoid and quantifiable within the saliva, urine, and plasma using cortisol assays for observing the effects of chronic and acute depression.…”
Section: Introductionmentioning
confidence: 99%